On Dimensionality, Measurement Invariance, and Suitability of Sum Scores for the PHQ-9 and the GAD-7 - Stochl, Jan; Fried, Eiko I; Fritz, Jessica; Croudace, Tim J; Russo, Debra A; Knight, Clare; Jones, Peter B; Perez, Jesus (Assessment, 2022)
In psychiatry, severity of mental health conditions and their change over time are usually measured via sum scores of items on psychometric scales. However, inferences from such scores can be biased if psychometric properties such as unidimensionality and temporal measurement invariance for instruments are not met. Here, we aimed to evaluate these properties for common measures of depression (Patient Health Questionnaire-9) and anxiety (Generalized Anxiety Disorder Assessment-7) in a large clinical sample (N = 22,362) undergoing psychotherapy. In addition, we tested consistency in dimensionality results across different methods (parallel analysis, factor analysis, explained common variance, the partial credit model, and the Mokken model). Results showed that while both Patient Health Questionnaire-9 and Generalized Anxiety Disorder Assessment-7 are multidimensional instruments with highly correlated factors, there is justification for sum scores as measures of severity. Temporal measurement invariance across 10 therapy sessions was evaluated. Strict temporal measurement invariance was established in both scales, allowing researchers to compare sum scores as severity measures across time.
Keywords: Psychometrics; Patient Health Questionnaire; úzkostné poruchy; measurement invariance; sebeposuzující dotazníky PHQ; PHQ-9; deprese; reprodukovatelnost výsledků; Reproducibility of Results; sum scores; úzkost; GAD-7; lidé; psychometrie; Anxiety Disorders; dimensionality; Humans; Depression; Anxiety